Teleworking and job performance: Perceptions of staff at a higher education institution - Ortiz-Huaman, Maria L. (2025)
The objective of this research was to understand staff perceptions of teleworking and its impact on job performance within a higher education institution. The research used a quantitative, applied approach and a non-experimental, correlational, and cross-sectional design. Data were collected through a questionnaire administered to a sample of 195 staff members at the institution. The results showed that 84% of respondents perceived their job performance in the context of teleworking as good, while 16% considered it average. It was also identified that teleworking is related to access to and use of information and communication technologies (ICTs), as well as the conditions of the physical workspace. These findings highlight the importance of establishing ideal conditions for the implementation and monitoring of teleworking, ensuring a favorable environment that allows for optimized job performance. In conclusion, access to appropriate technological resources and a suitable work environment contributes to enhancing job performance in the context of teleworking in higher education institutions.